Genetic Mutation Analysis in Small Cell Lung Cancer by a Novel NGS-Based Targeted Resequencing Gene Panel and Relation with Clinical Features. (7th April 2021) - Jin, Wang; Lei, Zhao; Xu, Sun; Fachen, Zhou; Yixiang, Zhang; Shilei, Zhao; Tao, Guo; Zhe, Sun; Fengzhou, Li; Su, Wen-Hui; Chundong, Gu
Abstract : Background . Small cell lung cancer (SCLC) is an aggressive and invasive malignancy that presents at advanced clinical stage with no more effective treatments. Development of a method for its early detection would be useful, also new therapeutic target need to be discovered; however, there is a lack of information about its oncogenic driver gene mutations. Objectives . We aim to identify the SCLC-related genomic variants that associate with clinical staging and serum protein biomarkers observed in other types of lung cancer. Methods . We screened formalin-fixed paraffin-embedded (FFPE) biopsy tissues of 32 Chinese SCLC patients using the 303 oncogenic driver gene panel generated by Tiling PCR amplification sequencing (tPAS) and analyzed the patients' corresponding serum protein levels of CYFRA21-1 CEA, NSE, and SCCA. Results . In total, we found 147 SCLC-related mutant genes, among these, three important genes ( TP53, RB1, KMT2D ) as well as five novel genes LRRK2, BRCA1, PTCH1, ARID2, and APC that altogether occurred in 90% of patients. Furthermore, increased mutations to 6 genes ( WT1, NOTCH1, EPHA3, KDM6A, SETD2, ACVR1B ) significantly associated with higher serum NSE levels (P = 0.0016 ) and higher clinical stages II + III compared to stage I (P = 0.06 ). Conclusions . Our panel is relatively reliable in detecting the oncogenic mutations of Chinese SCLC patients. Based on our findings, it may be possible to combine SCLC-related mutations and serum NSE for a simple detection of clinical staging.